Molecular and epigenetic alterations in normal and malignant myelopoiesis in human leukemia 60 (HL60) promyelocytic cell line model - Basu, Jhinuk; Madhulika, Swati; Murmu, Krushna Chandra; Mohanty, Smrutishree; Samal, Priyanka; Das, Asima; Mahapatra, Soumendu; Saha, Subha; Sinha, Indranil; Prasad, Punit (Frontiers in Cell and Developmental Biology, 2023)
In vitro cell line model systems are essential in supporting the research community due to their low cost, uniform culturing conditions, homogeneous biological resources, and easy experimental design to study the cause and effect of a gene or a molecule. Human leukemia 60 (HL60) is an in-vitro hematopoietic model system that has been used for decades to study normal myeloid differentiation and leukemia biology. Here, we show that IMDM supplemented with 20% FBS is an optimal culturing condition and induces effective myeloid differentiation compared with RPMI supplemented with 10% FBS when HL60 is induced with 1α,25-dihydroxyvitamin D3 (Vit D3) and all-trans retinoic acid (ATRA). The chromatin organization is compacted, and the repressive epigenetic mark H3K27me3 is enhanced upon HL60-mediated terminal differentiation. Differential gene expression analysis obtained from RNA sequencing in HL60 cells during myeloid differentiation showed the induction of pathways involved in epigenetic regulation, myeloid differentiation, and immune regulation. Using high-throughput transcriptomic data (GSE74246), we show the similarities (genes that did not satisfy |log2FC|>1 and FDR<0.05) and differences (FDR <0.05 and |log2FC|>1) between granulocyte-monocyte progenitor vs HL60 cells, Vit D3 induced monocytes (vMono) in HL60 cells vs primary monocytes (pMono), and HL60 cells vs leukemic blasts at the transcriptomic level. We found striking similarities in biological pathways between these comparisons, suggesting that the HL60 model system can be effectively used for studying myeloid differentiation and leukemic aberrations. The differences obtained could be attributed to the fact that the cellular programs of the leukemic cell line and primary cells are different. We validated several gene expression patterns for different comparisons with CD34+ cells derived from cord blood for myeloid differentiation and AML patients. In addition to the current knowledge, our study further reveals the significance of using HL60 cells as in vitro model system under optimal conditions to understand its potential as normal myeloid differentiation model as well as leukemic model at the molecular level.